Comecon, integration problems of the planned economies - Kaser, Michael Charles; Royal Institute of International Affairs (London ; New York : Oxford University Press, 1965)
The division of this study into two aspects of Comecon - history and current problems - is designed to follow the two chief lines of interest of western readers.
"Issued under the auspices of the Royal Institute of International Affairs."
Includes bibliographical references and index.
osc 14/11/2018
Loans
Keywords: International economic integration; Europe, Eastern